Odontogenic differentiation of dental pulp stem cells by glycogen synthase kinase-3β inhibitory peptides - Vidhyashree Rajasekar; Mohamed Mahmoud Abdalla; Mohammed S. Basbrain; Prasanna Neelakantan; Cynthia KY Yiu (Stem Cell Research & Therapy)
Abstract Background To investigate the effects of peptide-based substrate competitive inhibitors of GSK-3β (GSK-3βi) on promoting odontogenic differentiation of human dental pulp stem cells (hDPSCs). Methods The biocompatibility and proliferation of hDPSCs treated with GSK-3βi peptides (pS9, LRP 6a, L803, and L803-mts) were evaluated using the tetrazolium reduction assay and cell counting kit-8 assay, respectively. The differentiation of hDPSCs following peptide treatment was determined using the alkaline phosphatase assay (ALP), calcium mineralization (alizarin red staining), and quantification of mRNA expression of differentiation markers via quantitative real-time polymerase chain reaction. The accumulation of β-catenin in the nucleus of GSK3-βi-treated hDPSCs was determined using immunofluorescence staining. The effect of peptide treatment on hDPSC migration was characterized using the transwell assay. Results All tested concentrations of the peptides were found to be biocompatible with the hDPSCs, with no significant difference compared to the control (p > 0.05). The peptides had no effect on the proliferation of hDPSCs compared to the control (p > 0.05). However, all the tested peptides significantly increased ALP activity and calcium deposition in a dose-dependent manner (p < 0.05). Specifically, L803-mts showed significantly greater ALP activity and mineralization compared to the other peptides and the controls (p < 0.05). Additionally, L803-mts showed a significant increase (p < 0.05) in the expression of DSPP, DMP-1, Runx-2, along with increased protein expression of DSPP and DMP-1 compared to the control. Furthermore, it enhanced the nuclear translocation of β-catenin and increased the chemotactic migratory potential of hDPSCs. Conclusions L803-mts, a peptide-based substrate competitive inhibitor of GSK-3β, enhanced the odontogenic differentiation of hDPSCs by activating the Wnt signaling pathway.